2018
DOI: 10.1108/aeat-08-2017-0191
|View full text |Cite
|
Sign up to set email alerts
|

The airbus A320 family fan cowl door safety modification: a human factors scenario analysis

Abstract: Purpose-The Airbus A320 family engine fan cowl doors safety issue is known to the industry for almost 18 years, however it has not been addressed adequately by the aircraft manufacturer and the various operators and regulating authorities. This brief case study paper examines in a systematic way the possible operational and safety implications of a new modification on the engine fan cowl doors. Design/methodology/approach-An array of error-prone scenarios are presented and analysed under the prism of human fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
(12 reference statements)
0
6
0
Order By: Relevance
“…One of the 'planes' in Reason's (1990) original iteration of the Swiss Cheese model was labeled "fallible decisions", Kourousis, et al [40] identified the increased defenses the manufacturer of the A32X series of aircraft inserted into the safety system in the aftermath to this accident in an effort to reduce or eliminate the occurrences of cowl doors not being fully latched at take-off. Mandated modifications included new hardware and new procedures.…”
Section: Active Failures and Latent Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the 'planes' in Reason's (1990) original iteration of the Swiss Cheese model was labeled "fallible decisions", Kourousis, et al [40] identified the increased defenses the manufacturer of the A32X series of aircraft inserted into the safety system in the aftermath to this accident in an effort to reduce or eliminate the occurrences of cowl doors not being fully latched at take-off. Mandated modifications included new hardware and new procedures.…”
Section: Active Failures and Latent Conditionsmentioning
confidence: 99%
“…Mandated modifications included new hardware and new procedures. However, the authors noted the potential latent failings that could arise from these newly implemented modifications [40]. These latent conditions arising from fallible decisions made by people who are not proximal to the accident may hinder or even work directly against the desired effect of reducing the number of cowl door incidents the mandated modifications are seeking.…”
Section: Active Failures and Latent Conditionsmentioning
confidence: 99%
“…For this purpose, the case study presented next is selected to present the operation of the DiCTAM model, as well as exemplifying its use. A well-known case has been selected, that of the engine fan cowl door losses experienced in the Airbus A320 family fleet in worldwide level [56]. The method of the case study is considered to be suitable method to examine hypothetical scenarios.…”
Section: Phasementioning
confidence: 99%
“…The method of the case study is considered to be suitable method to examine hypothetical scenarios. A suitable application for the prediction exercise is deemed the use of the Fan Cowl Doors (FCDs) maintenance occurrences (after the implementation of the new procedures, provisioned by the latest EASA Airworthiness Directives (ADs)) [56]. The case study methodology assists in the holistic examination of these hypothetical occurrences to unveil concealed elements and identify or even predict future trends or patterns [57].…”
Section: Phasementioning
confidence: 99%
See 1 more Smart Citation